2006
DOI: 10.1677/joe.1.06866
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization, and quantitative expression analysis of rainbow trout myostatin-1a and myostatin-1b genes

Abstract: Myostatin is a potent negative regulator of skeletal muscle growth. Although several cDNA clones have been characterized in different vertebrates, the genomic organization and bioactivity of non-mammalian homologs have not. The intron/exon organization and promoter subsequence analysis of two rainbow trout myostatin genes, rtMSTN-1a and rtMSTN-1b (formerly 1 and 2 respectively), as well as a quantitative assessment of their embryonic, larval, and adult tissue expression profiles are reported herein. Each gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 37 publications
(46 reference statements)
2
68
0
2
Order By: Relevance
“…Both transcripts were nearly undetectable during gastrulation. This indicates that neither is necessary at this stage and is consistent with previous assessments of developing embryos from different fish species including tilapia (Rodgers et al, 2001), zebrafish (Biga et al, 2005), rainbow trout (Garikipati et al, 2006), brook trout (Roberts and Goetz, 2003) and even in mammals. Indeed, in situ hybridization studies of myostatin expression in mice determined that it is first detected in the myotome compartment of somites .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Both transcripts were nearly undetectable during gastrulation. This indicates that neither is necessary at this stage and is consistent with previous assessments of developing embryos from different fish species including tilapia (Rodgers et al, 2001), zebrafish (Biga et al, 2005), rainbow trout (Garikipati et al, 2006), brook trout (Roberts and Goetz, 2003) and even in mammals. Indeed, in situ hybridization studies of myostatin expression in mice determined that it is first detected in the myotome compartment of somites .…”
Section: Discussionsupporting
confidence: 90%
“…Curiously, the selective knockdown of MSTN-1 expression with antisense morpholino oligonucleotides was reported to increase the expression of some muscle-specific genes at 10 hpf and to increase the developmental rate and size of somites (Amali et al, 2004)-a surprising finding given that (1) zfMSTN-1 expression is virtually undetectable at this developmental time and lower than the corresponding level of zfMSTN-2 expression (Fig. 3) and (2) that other studies of zebrafish (Kerr et al, 2005), tilapia (Rodgers et al, 2001), rainbow trout (Garikipati et al, 2006 ), brook trout (Roberts and Goetz, 2003) and even mice all suggest that myostatin is not expressed during gastrulation. Xu et al (2003) also generated null fish by overexpressing a dominant-negative zfMSTN-1 (i.e.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Most bony fish species possess at least two myostatin genes (MSTN-1 and -2; Kerr et al 2005) as a result of early genome duplication events , Postlethwait et al 1998, while rainbow trout and other salmonids have four due to their recent tetraploidization (Postlethwait et al 1998, Kerr et al 2005, Garikipati et al 2006. Although MSTN-2b is a pseudogene, functions of the other paralogs are presumably intact and each gene is differentially expressed in a tissue-and developmental-specific manner (Rodgers & Garikipati 2008).…”
Section: Introductionmentioning
confidence: 99%
“…CAST is an endogenous inhibitor of Ca 2+ -dependent protease (Barnoy et al, 1997). Garikipati et al (2006) reported the widespread expression of MSTN in over twenty tissues of rainbow trout and especially high level in spleen and eyes. In the present experiment, the expression of MSTN was also observed in all tissues examined.…”
Section: Discussionmentioning
confidence: 99%